Aplikasi Model Konservasi Levine dalam Asuhan Keperawatan Untuk Pemenuhan Kebutuhan Oksigenasi di Rumah Sakit - Deswita (NERS Jurnal Keperawatan, 2012)
This case study showed the description about aplication of Levin Conservation Model for children with oxygenation impaired in hospital. The aims of Levin Conservation Model is to optimalized client’s adaptation who has the problem with oxygenation in the environment to reach the wholeness health. The primary nursing diagnose cached was the in efective airway breathing and impaired airway changes. Nursing intervention which was given are positioning the client in order to maximalized retraction of lung and optimalizating oxygen’s supply into the whole-body system, monitoring oxygenation status, giving health education and supporting system of family to the client.